The cosmic landscape : string theory and the illusion of intelligent design - Susskind, Leonard (Little, Brown and Co, 2006)
In The Cosmic Landscape (Little, Brown, 2005), Leonard Susskind offers a different conception. The Stanford physicist champions the idea of a "megaverse," a sea of pocket universes whose local environments correspond to the myriad solutions offered by string theory. Rather than seek a unique theory that somehow allows for our existence, he argues, physicists should consider a landscape of parallel universes in which the "local weather" is, here and there, hospitable to life. The landscape idea has sparked an ongoing debate. American Scientist Online managing editor Greg Ross interviewed Susskind by e-mail in December 2005.